Penerapan Media Augmented Reality Untuk Visualisasi Organ Tubuh Manusia di SMAS Dwi Putra - Imam Baihaqi Al Rosyid; Rikaro Ramadi; Yasin Efendi; Adi Alam (MES Bogor, 2026)
This study aims to develop Augmented Reality (AR)-based learning media to facilitate the visualization of human organs in high school Biology instruction. The research background stems from students’ low comprehension of organ structures and functions, as well as the limited availability of interactive learning media in schools. The study employs a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. The final product is an Android-based mobile application that presents 3D models of human organs through marker scanning. Validation results indicated that the media was rated as highly feasible by both material experts and media experts with a score of 100%, while student trials revealed a positive response with a score of 85%, categorized as highly feasible. These results confirm that the developed AR media is valid, practical, and effective in enhancing students’ understanding of human organs. The implication of this research is that AR can serve as an innovative alternative for developing Biology learning media in high schools.